Effect of Perceived Intimacy on Social Decision-Making in Patients with Schizophrenia - Park, Sunyoung; Shin, Jung Eun; Han, Kiwan; Shin, Yu-Bin; Kim, Jae-Jin (Frontiers in Human Neuroscience, 2014)
Social dysfunctions including emotional perception and social decision-making are common in patients with schizophrenia. The aim of this study was to determine the level of intimacy formation and the effect of intimacy on social decision in patients with schizophrenia using virtual reality tasks which simulate complicated social situations. Twenty-seven patients with schizophrenia and 30 healthy controls performed the two virtual social tasks: the intimacy task and the social decision task. The first one was to estimate repeatedly how intimate participants felt with each avatar after listening to what avatars said. The second one was to decide whether or not participants accepted the requests of easy, medium or hard difficulty by the intimate or distant avatars. During the intimacy task, the intimacy rating scores for intimate avatars were not significantly different between groups, but those for distant avatars were significantly higher in patients than in controls. During the social decision task, the difference in the acceptance rate between intimate and distant avatars was significantly smaller in patients than in controls. In detail, a significant group difference in the acceptance rate was found only for the hard requests, but not for the easy and medium difficulty requests. These results suggest that patients with schizophrenia have a deficit in emotional perception and social decision-making. Various factors such as a peculiarity of emotional deficits, motivational deficits, concreteness, and paranoid tendency may contribute to these abnormalities.